2016
DOI: 10.1159/000449101
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Impairs Apoptosis of Nasal Epithelial Cells in Asthma via HSP70

Abstract: Asthmatics are highly susceptible to respiratory viral infections, possibly due to impaired innate immunity. However, the exact mechanisms of susceptibility are likely to differ amongst viruses. Therefore, we infected primary nasal epithelial cells (NECs) from adults with mild-to-moderate asthma, with respiratory syncytial virus (RSV) or human metapneumovirus (hMPV) in vitro and investigated the antiviral response. NECs from these asthmatics supported elevated hMPV but not RSV infection, compared to non-asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Not all studies investigating impaired interferon production in asthmatic patients are in agreement, with several studies failing to show any difference in interferon production between cells from asthmatic patients and those from control subjects. [38][39][40][41][42][43] Reasons for this disparity mostly concern studies of primary HBECs, which are cultured in vitro for several weeks before infection and study. Differences in the above findings are likely due to several variables, including differences in viral strains used or their preparation, 44 cell-culture methods (eg, different components of medium), or methods of propagation, 39 and also recruitment and phenotype of asthmatic subjects, including the asthma severity, asthma control 43 and atopic status.…”
Section: Limitations and Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all studies investigating impaired interferon production in asthmatic patients are in agreement, with several studies failing to show any difference in interferon production between cells from asthmatic patients and those from control subjects. [38][39][40][41][42][43] Reasons for this disparity mostly concern studies of primary HBECs, which are cultured in vitro for several weeks before infection and study. Differences in the above findings are likely due to several variables, including differences in viral strains used or their preparation, 44 cell-culture methods (eg, different components of medium), or methods of propagation, 39 and also recruitment and phenotype of asthmatic subjects, including the asthma severity, asthma control 43 and atopic status.…”
Section: Limitations and Controversiesmentioning
confidence: 99%
“…28 More studies with comparisons of rhinovirus with other respiratory viruses clearly need to be performed to better understand whether the defect in interferon expression is virus specific. Likewise, studies of impaired interferon production in nasal epithelial cells from asthmatic patients have produced mixed results, 41,45,46 suggesting that deficiency might be more profound in lower airway cells, yet deficiency is still observable in peripheral leukocyte populations. 28,32,47 The role of atopy is perplexing; Baraldo et al 34 showed that deficient interferon production was a feature of atopic asthmatic, nonatopic asthmatic, and nonasthmatic atopic children, 34 and studies focusing on allergic rhinitis without asthma have produced mixed results, 4,52 furthering the debate about whether it is asthma or atopy (or both) that drives this defect.…”
Section: Limitations and Controversiesmentioning
confidence: 99%
“…A general indication that the Hsp70s play a role in the replication of the Mononegavirales is provided by the induction of Hsp70 during infection with certain members of this virus order [51,52,53,54,55,56,57,58,59], and the co-localization of these chaperones to sites of viral replication (cytoplasmic inclusion bodies) in cells infected with canine distemper virus (CDV) [60], RSV [61,62], RABV [53,63], and MuV [51]. Early studies showed that pretreatment of cells with acute heat stress, which upregulates numerous chaperones, including Hsp70, increased the polymerase transcription of NC purified from cells infected with either MeV or the related CDV [64,65,66,67].…”
Section: Chaperone–mononegavirales Interactionsmentioning
confidence: 99%
“…Several different Hsp70 inhibitors have been described that target the ATP binding domain (e.g., VER155008, as well as MKT007 and its derivatives YM1 and JG40) and the substrate binding domain (pifithrin-μ). While these have been shown to reduce replication in the context of mini-genomes or other surrogates of viral replication for EBOV [76,77], RSV [79], and MPV [55], the potency of these inhibitors appears to be less than those targeting Hsp90. Indeed, for MeV and MuV, Hsp70 inhibitors did not influence replication [80]; however, despite not showing antiviral effect on its own, the Hsp70 inhibitor VER155008 was shown to strongly potentiate the antiviral activity of Hsp90 inhibitors for both viruses [80], suggesting that combinatorial chaperone inhibition may be a promising antiviral approach.…”
Section: Chaperone Inhibitors As Antiviralsmentioning
confidence: 99%
“…VER155008, as well as MKT007 and its derivatives YM1 and JG40) and the substrate binding domain (pifithrin-). While these have shown to reduce replication in the context of mini-genomes or other surrogates of viral replication for EBOV [67,68], RSV [70], and MPV [109], the potency of these inhibitors appears to be less than that of Hsp90 inhibitors. Indeed, for MeV and MuV, Hsp70 inhibitors did not influence replication [72].…”
Section: Chaperone Inhibitors As Antiviralsmentioning
confidence: 99%